A Comprehensive Diagnosis of Components of Pedagogical Students’ Research Competency - O. S. Andreeva; O. A. Selivanova; I. V. Vasilieva (Obrazovanie i Nauka, 2019)
Introduction. Nowadays, the aspects of development of research competencies in future experts belong to the most relevant topics, which are widely being discussed both in Russian and in foreign scientific community. One of burning issues in this thematic block is diagnosis of such competencies without which their successful development is impossible. Today, we are witnessing the disparity between a large number of the methods presented in scientific sources and technologies of the formation of students’ research competency and limitation of its criteria and indicators. Moreover, there is lack of adequate methodological tools to estimate objectively the level and quality of scientific literacy and degree of students’ research activity.The aim of the research was to define the content of a comprehensive diagnosis of the components of pedagogical students’ research competency and to justify the criteria, indicators and methods of its evaluation.Methodology and research methods. The methods of analysis, synthesis, generalisation and modelling were employed. The systematic approach was applied, taking into account the provisions of plurality, integrity and structurisation.Results and scientific novelty. The authors presented and described the model of formation of pedagogical students’ practice-focused research competency. The knowledge-based, value-oriented and practical components of the model are correlated to the methods of psycho-pedagogical monitoring, which are relevant to the content of these components. The complex of particular techniques for comprehensive, precise and complete assessment of future teachers’ research competency is designed. The complexity of measurement tools is provided with homogeneity between a theoretical construct (research competency) and operationalised constructs (psychological phenomena estimated in diagnostic techniques). Cumulative application of the selected diagnostic procedures and techniques allows: objective and subjective indicators of formation of research abilities and skills to be compared; motivation and readiness of students for implementation of independent research activity to be defined, taking into account social and professional contexts of its realisation.Practical significance. The authors of the present publication propose to introduce into practice of the higher school the approaches to contents, structure and organisation of the psychological diagnostics of level of students’ research competency, which will give the chance not only to carry out the internal regular and continuous monitoring of formation of one of key characteristics of the identity of the modern expert in educational institutions, but also to optimise the process of multilevel high school preparation, having adjusted work on early identification of its problems and crisis stages to take timely effective correctional measures.